THE LEXEME SOUL IN THE NATIONAL-SPIRITUAL EPICAL DISCOURSE OF BOHDAN LEPKY - Komarova, Zoia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The expressive possibilities of the lexeme soul in Bohdan Lepky’s artistic discourse have been discussed in the article. Based on the analysis of the peculiarities of the functioning of this lexeme through the prism of the author’s worldview, it was found that the writer’s language creation is characterized by an appeal to the linguistic image of the soul as a verbal representative of the inner psycho-emotional world of the characters. The soul in the prose texts of B. Lepky denotes the place of localization of human emotions and feelings, thoughts and desires, as well as the person himself with his traits and qualities, reveals the ability to reflect the human inner essence, it is closely related to intellectual processes but is more often used metaphorically reinterpreted phrases with the meaning of feeling. The writer often resorts to the use of common language phraseology with a soul component as well as to their partial modification, the introduction of individually authorial verbal expressions that reveal the specifics of drawing the image of the soul. Phraseologisation of the psycho-emotional state of the characters is achieved by personification and metaphorization of the soul as the spiritual and emotional basis of a person. Verbal type of metaphor prevails in author’s descriptions. Metaphorical epithets for the lexeme soul in the texts under the analysis are objectified with the help of adjectives and adjectives, they record B. Lepky’s ideas about the moral and ethical values ​​of a person, characterize the characters as bearers of personal traits and qualities. In the works of the writer, the lexeme soul acquires a certain symbolic meaning being associated with darkness and light, cold and heat, black and white colors, the linguistic expression of which is conveyed with the help of metaphors and phraseological units. The soul is perceived as a voluminous thing with a bottom and depths, where a person hides his secret thoughts and feelings. The writer actualizes the sacred understanding of the soul only in isolated contexts.